Perancangan Sistem Alarm Kebisingan untuk Kapal Penangkap Ikan Berbasis Arduino Uno dengan Sensor KY-037 - Muhammad Romdonul Hakim; Anas Noor Firdaus; M Kamal Abdal Nasser (Yayasan Literasi Sains Indonesia, 2024)
Fishermen are highly susceptible to hearing impairment due to prolonged exposure to the high-intensity noise of boat engines. While numerous studies have investigated the noise intensity levels of boat engines, no research has been conducted on noise warning alarm systems for fishing boats. Therefore, this study aims to develop a sound noise alarm system based on Arduino Uno with a KY-037 sensor for fishing boats, which is expected to reduce the potential for hearing impairment among fishermen. This research employs a quantitative descriptive approach, with data collected through experimental methods and analyzed by comparing noise level data at various engine speeds. The results of the noise level measurements of boat engines at the Fish Landing Base (PPI) in Cikidang, Pangadaran Regency, indicate that the majority of fishermen are safe from hearing impairment due to engine noise, as most boats there are small, with a Gross Tonnage (GT) capacity of under 5 GT. The risk of hearing impairment emerges for boats with a capacity of 11 GT running at a maximum engine speed of 1600 rpm, producing noise levels up to 84 dB. Thus, it is recommended that crew members use earplugs.